Community participation: greening the Aba Gerima watershed in Ethiopia - Mandapati, J. (CGIAR Research Program on Water, Land and Ecosystems, 2021)
The Aba Gerima watershed covers the upper portion of Lake Tana sub-basin in north-western Ethiopia. Agriculture is its mainstay, with cereal cultivation occupying about 60% of 984 hectares. But the ecology of the landscape is threatened by the conversion of natural vegetated land to cropland, and continuing land degradation has been affecting the livelihoods of farmers.